WAKAF TUNAI UNTUK PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - Purbowanti, Anifah; Muntaha, Dani (ZISWAF, 2017)
Education is the key to the progress of a nation. A nation whose quality of education is low, will be slumped and left behind from other nations. Conversely, a nation whose education is advanced, will excel from any nation. Indonesia is a country whose quality of education is very low. Economic crisis that plagued this country, increasingly difficult for the people of Indonesia to advance and improve the quality of education. The condition of poverty that menggurita which resulted in the worsening of education of the ummah, must be overcome immediately. This article discusses about the implementation of cash waqf (endowment) in Indonesia and its role in strengthening education. Cash waqf plays a significant role in some Islamic education institutionin providing material support. One example is Pondok Pesantren Gontor in East Java.